Diversity in risk communication - Probohudono, A.; Tower, Gregory; Rusmin, Rusmin (University of Wollongong, 2013)
This study analyses the communication of the five major categories of risk (business, strategy,market and credit risk disclosure) over the volatile 2007-2009 Global Financial Crisis (GFC) timeperiod in key South East Asian countries’ manufacturing listed companies. This study is importantas it contributes to the literature by providing insights into the voluntary risk disclosure practicesusing sample countries with different economic scenarios. Key findings are that business risk is themost disclosed category and strategy risk is the least disclosed. Business and credit risk disclosureconsistently increase over the three year period, while operating, market and strategy risk disclosureincrease in 2008, but then decrease slightly in 2009. Statistical analysis reveals that country ofincorporation and size help predict risk disclosure levels. The overall low disclosure levels (26-29%) highlight the potential for far higher communication of key risk factors.